Pengaruh Kualitas Pelayanan SIAKAD terhadap Kepuasan Mahasiswa pada Fakultas Teknik Sipil dan Perencanaan, Institut Teknologi Nasional (ITN) Malang - Haning Tri Novianti; Yaqub Cikusin; Slamet Muchsin; Dimas Indra Laksmana (Jayapangus Press, 2026)
The rapid advancement of information technology has encouraged higher education institutions to deliver academic services through effective and responsive digital platforms, particularly Academic Information Systems (SIAKAD). Nevertheless, the presence of such systems does not automatically ensure high levels of student satisfaction, as service quality remains a decisive factor in shaping user experience. This study aims to examine the influence of SIAKAD service quality on student satisfaction at the Faculty of Civil Engineering and Planning, Institut Teknologi Nasional (ITN) Malang. An explanatory quantitative design was employed, involving 71 respondents selected through accidental sampling based on the Slovin formula. Service quality was operationalized using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Student satisfaction was assessed by measuring the alignment between expectations and perceived performance. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with IBM SPSS. The findings reveal that, collectively, SIAKAD service quality exerts a significant effect on student satisfaction (F = 83.095; p < 0.001), with a coefficient of determination (R²) of 0.865, indicating a strong explanatory power of the model. Partially, all five dimensions demonstrate positive and significant contributions, with responsiveness emerging as the most influential factor (β = 0.408), followed by empathy (β = 0.336), assurance (β = 0.222), tangibles (β = 0.218), and reliability (β = 0.204). These results underscore that prompt responses, clear academic information, and attentive support play a central role in shaping students’ perceptions of satisfaction. Strengthening service quality and enhancing responsiveness are therefore essential strategies for fostering student satisfaction and reinforcing effective digital governance in higher education institutions.